Implementasi Sistem Pengendalian Internal Revitalisasi Pasar Desa Mertapada - Permana, Ipik; Siswoyo, Mukarto; Ma’rifat , Ifa Elmu (Jayapangus Press, 2022)
The Internal Control System is a system designed to achieve organizational goals effectively and efficiently, the reliability of presenting financial reports, and compliance with government regulations. This research aims to obtain an overview of the internal control system in the revitalization of the Mertapada Kulon village market, to find out the obstacles faced in the internal control system for the revitalization of the Mertapada Kulon village market, and to find out the appropriate strategy in the internal control system for the revitalization of the Mertapada Kulon village market in Cirebon Regency. This study uses a qualitative method. The research strategy in the qualitative approach that the author uses is a case study strategy. The research was carried out at the Mertapada Kulon Village Market, which is located on Jalan Wahid Hasyim, Mertapada Kulon, Astana Japura District, Cirebon Regency. Interview collection techniques, observations, and interviews Data analysis includes data reduction, data presentation, and drawing conclusions. The results of the research show that overall, the internal control system in the revitalization of the Mertapada Kulon village market is in accordance with its implementation. Obstacles in the form of internal factors are the limited government budget, the fact that there are several traders who want to revitalize the market with only one floor, and the lack of firmness on the part of the revitalization committee in arranging the layout. kiosk on the first floor. The external factors that hindered this were natural factors (rainy weather), there were several community parties who did not approve of the revitalization program, and the processing of permit documents from the relevant agencies took up to 4 months. By using SWOT analysis, the diversification strategy is able to optimize the internal control system for revitalizing the Mertapada Kulon village market by maximizing strengths and opportunities while simultaneously minimizing the weaknesses and threats faced.